Kajian Intrusi Air Laut Pada Sumur Dangkal Di Desa Denai Kuala Kecamatan Pantai Labu Kabupaten Deli Serdang (Study Of Seawater Intrusion At Shallow Wells In The Denai Kuala Village, District Of Pantai Labu Regency Of Deli Serdang) - Santa Odilia Permatasari Nainggolan; Pindi Patana; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
The increase of population in the coastal area affects in exploitation of ground water . Shallow well is one of the media that be used to fulfill the needs of water. The location of ground water that closed to coastal area, caused the sea water intrution and then shallow well water changed into brackish and salty. The aim of this research is to analyze the salinity of shallow well water and mapping the distribution shallow well water. This research was done in Denai Kuala village district of Pantai Labu, Deli Serdang on May until June 2015. The water sample was taken randomly with 80 samples of shallow well water spread in four station. This research uses the Arc GIS 9.3 software to obtain a map of the spread of salinity. Spread show that the salinity of the shallow well water in the Denai Kuala village varied. Salinity of shallow well at station 1 is 0 mg/l ( category fresh water), at station 2 is 2250 mg/l ( category brackish water), at station 3 is 0 mg/l (category fresh water), and at station 4 is 3150 mg/l (category brackish water). The spread of salinity show that the biggest of sea water intrusion are on the station 2 and station 4, while on the station 1 and station 3 have not been affected by seawater intrusion.Keywords : Seawater Intrusion, Salinity, Shallow Wells.PENDAHULUANPertumbuhan penduduk semakin meningkat sepanjang